A game for virtual reality players - Tan, Wei Ang (Nanyang Technological University, 2023)
Virtual Reality (VR) is slowly increasing in popularity due to the demand for Virtual Reality game and the demand was driven by the adoption of VR hardware among gamers. Another reason is that VR headset are now more affordable for more consumers. In addition to that, the market for VR game is predicted to increase over the years. Moreover, VR games tend to be more immersive than traditional computer games due to realistic experience as compared to playing the game from a physical screen. Recently, BoneLabs, a physics-based VR game, has shown the world the possibility of VR games. Ranging from parkouring to changing character models, BoneLabs can do things that VR games has not presented before. As a result, VR games has endless possibilities, with the restriction being human’s creativity and current technology. Therefore, this project aims to develop a VR game which is a rogue-like dungeon crawler game. This will engage the players and allow them to have an enjoyable experience while playing the game. This report documents on the various features and implementation of the game, as well as the reasoning behind certain features. At the end of the project, an early beta test was conducted to check if the players find the game enjoyable.